Fishmeal, plant protein, and fish oil substitution with single-cell ingredients in organic feeds for European sea bass (Dicentrarchus labrax) - Vasilaki, A.; Mente, E.; Fountoulaki, E.; Henry, M.; Nikoloudaki, C.; Berillis, P.; Kousoulaki, K.; Nengas, I. (Frontiers in Physiology, 2023)
Single cell ingredients (SCI) are considered promising nutrient sources which are produced using environmentally friendly biotechnological processes. The aim of the current study was the evaluation of replacing fishmeal, plant protein sources and fish oil by single cell ingredients in organic feeds for European sea bass (Dicentrarchus labrax). Bacterial protein, yeast protein and microalgae were used to replace fishmeal trimmings, soya bean meal and fish oil from trimmings. Triplicate groups (30 fish per replicate) of European sea bass (14.4 ± 2.4g) fed the experimental diets for 71 days. Results showed that incorporation of SCI at all levels of inclusion significantly enhanced nutrient digestibility. Additionally, growth performance parameters were not affected by SCI inclusion, exhibiting similar or improved values. Moreover, a tendency for improved anterior and posterior gut structure was observed and a significant increase of lysozyme activity at the two highest inclusion levels of SCI was determined. Overall the results showed that inclusion of single cell ingredients at 15% (bacterial: yeast: algae - 9.4: 4.7: 1) is possible without compromising any of the parameter evaluated. According to these findings a higher substitution of fishmeal trimmings, plant protein sources and fish oil from trimmings can be further evaluated, in future studies, by single cell ingredients in organic diets for European sea bass (Dicentrarchus labrax).